2019
DOI: 10.1016/j.ebiom.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SLC25A11 causes suppression of NSCLC and melanoma tumor formation

Abstract: BackgroundFast growing cancer cells require greater amounts of ATP than normal cells. Although glycolysis was suggested as a source of anabolic metabolism based on lactate production, the main source of ATP to support cancer cell metabolism remains unidentified.MethodsWe have proposed that the oxoglutarate carrier SLC25A11 is important for ATP production in cancer by NADH transportation from the cytosol to mitochondria as a malate. We have examined not only changes of ATP and NADH but also changes of metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…This markedly lowered ATP production and inhibited the growth of cancer cells, which was not observed in normal cells. [22]. These findings suggest that MAS is a major contributor to ATP production in cancer.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This markedly lowered ATP production and inhibited the growth of cancer cells, which was not observed in normal cells. [22]. These findings suggest that MAS is a major contributor to ATP production in cancer.…”
Section: Introductionmentioning
confidence: 82%
“…We found that cancer cells prefer to use cytosolic NADH as an electron donor for ATP production through electron transfer complex [12][13][14][19][20][21][22]. To block the transfer of cytosolic NADH into mitochondria, we knocked down SLC25A11, the mitochondrial 2-oxoglutarate/malate carrier protein in the malate aspartate shuttle (MAS).…”
Section: Introductionmentioning
confidence: 99%
“…Mucosal melanoma of the head and neck (HNMM) region constitutes 55% of all mucosal melanomas, but <10% of all melanomas of the head and neck region. A majority of these tumors are found in the sinonasal regions (55%), while the rest are located in the oral cavity (25-40%) [13][14][15][16]. Mucosal melanomas generally present at a later stage, are more aggressive and carry a worse prognosis regardless of the stage at diagnosis [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Diagnosismentioning
confidence: 99%
“…Among sinonasal cases, approximately 80% are located in the nasal cavity itself, most commonly the middle and inferior turbinates, lateral nasal wall and nasal septum, while 20% occur in the paranasal sinuses [13,15,16].…”
Section: Primary Mucosal Melanomas Of the Nose And Paranasal Sinusesmentioning
confidence: 99%
“…GSH is a key member of cell immune response system, lacking it can easily lead to cell death, several labs have confirmed its common occurrence in all cancers (41) and considered it as potential therapeutic target. Besides, the loss of SLC25A11, the enzyme catalyzing these reactions, has been validated to inhibit tumor cell growth in non-small cell lung cancer (42). Baulies et al (43) suggested that the over-expression of SLC25A11 works as an adaptive mechanism of HCC to provide enough GSH for vast cell growth, meanwhile, SLC25A11 induced exportation of AKG to cytosol also activates mTOR pathway to promote cell growth and anabolism through EGLNs (egl-9 family hypoxia-inducible factors) (44).…”
Section: Enhancement Of Glutathione and Fatty-acid Biosynthesis Is Immentioning
confidence: 99%